ANALISA PEMBELIAN BARANG UNDERPRICED SEBAGI BENTUK KESALAHAN DELIK PENADAHAN: TINJAUAN YURIDIS YURISPRUDENSI MAHKAMAH AGUNG NOMOR 2/YUR/PID/2018 - Salim, Vina Putri; Ningrum, Tsamara Probo; Pratama, Risma Cahya Yudita; Fadilah, Nur (Universitas Gorontalo, 2020)
The purpose of this article is to find out the application of Supreme Court Jurisprudence Number 2 / Yur / Pid / 2018 which provides legal rules related to underpriced purchases as the fulfillment of the element